Karakteristik Morfologi Lichen Crustose Di Kawasan Hutan Sekipan Desa Kalisoro Tawangmangu Karanganyar Provinsi Jawa Tengah - Utari, Ratih Tri, Efri Roziaty, S. Si., M. Si sel (2017)
Morphology crustose lichen in the forest area sekipan was held on 2 and 9 April 2017. This study aims to determine the morphology of crustose lichen that grows on State forest Sekipan Karanganyar. This research uses descriptive quantitative survey techniques. This method establishes five different heights, namely 1100, 1200, 1300, 1400, 1500 m above sea level. There are six species of lichen crustose ie from Graphis scripta from Family Graphidaceae, Phlyctis argena of Family Phlyctidaceae, Lecidella elaechroma of Family Lecidellalaceae, Lepraria sp from Family Stereocaulaceae, Cryptothecia striata of Family Arthoniaceae, Lecanora sp of Family Lecanoraceae. The morphological characteristics of type crustose has a shape like crust (hard skin) flat, thin and attached to the surface of the tree that are difficult to be removed without damaging the substrate. Altitude affects the distribution of lichen, meaning that the higher the altitude the more numerous and varied the crustose lichen colonies.